Post‐release monitoring of Antillean manatees: an assessment of the Brazilian rehabilitation and release programme. (22nd September 2015) - Normande, I. C.; Malhado, A. C. M.; Reid, J.; Viana, P. C.; Savaget, P. V. S.; Correia, R. A.; Luna, F. O.; Ladle, R. J.
Abstract: Mammalian reintroduction programmes frequently aim to reconnect isolated sub‐populations and restore population viability. However, these long‐term objectives are rarely evaluated due to the inadequacy of post‐release monitoring. Here, we report the results of a unique long‐term telemetry‐based monitoring programme for rehabilitated Antillean manatees T richechus manatus manatus reintroduced into selected sites in north‐east Brazil with the aim of reconnecting isolated relict populations. Twenty‐one satellite‐tagged rehabilitated manatees, 13 males and 8 females, were released into the wild from two sites between November 2008 and June 2013. Individual accumulation curves were plotted and home ranges were calculated through the fixed kernel method using 95% of the utilization distribution. The number and size of the centres of activity (COAs) were calculated using 50% of the utilization distribution. Manatees displayed a dichotomous pattern of movement, with individuals either characterized by sedentary habits or by much more extensive movements. Moreover, home‐range size was not significantly influenced by gender, age at release or release site. COAs were strongly associated with sheltered conditions within reefs and estuaries, and also by the presence of freshwater and feeding sites. Our data confirm that manatee reintroductions in Brazil have the potential to reconnect distant sub‐populations. However, pre‐release identification of potential long‐distance migrants is currently unfeasible, and further analysis would be required to confirm genetic mixing of distant sub‐populations.